Mexico: as close to the United States as to Asia Pacific (2015)
The rapid economic growth, industrial development and high level of competitiveness have made Asia Pacific one of the most dynamic and, therefore, promising regions of the new century. In parallel, Mexico has been characterized as a country with an important economic muscle and with good projections; nevertheless, the changes derived from the transfer of power from one party to another at the end of the year 2000, caused a change in its international actions. In this sense, the interest of this article is to analyze the reorientation of Mexican economic and commercial policy in Asia Pacific, through the implementation of economic diplomacy between 2000 and 2012 and the most relevant aspects that resulted from the implementation of economic diplomacy , as trade agreements, memorandum of understanding, among others.